PENGARUH PENGGUNAAN SLIDE POWERPOINT TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SDN 34 PONTIANAK KOTA - Makmun, Syukron; Tampubolon, Budiman; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to analysis the influence of used slide powerpoint to student’s learning result of mathematics in grade IV SD Negeri 34 Pontianak City. The research method is used experiment with quaisy experiment design and the research design is used non-equivalent control group design. The sample of this research is 71 students of IVc and IVd SD Negeri 34 Pontianak City. The result of data analysis is to be found out influence of used slide powerpoint to student’s learning result of mathematics in grade IV SD Negeri 34 Pontianak City. The based on t-count is 2,064 to be found out influence of independent variable (X) to un-independent variable (Y). If to compare with t-table of rank significant 5% at 1,669. So, t-count more than to t-table (2,064 > 1,669) that so Ha is acceptance. Calculation of effect size of this research is to be found out influence of variable X to variable Y is 0,35. Keywords: Pengaruh, Slide PowerPoint, Hasil Belajar